Rapid RT-PCR amplification from limited cell numbers. - Edmands, S; Kirk, J; Lee, A; Radich, J (Genome Research, 1994)
We describe a rapid and efficient RT-PCR method particularly suited to procedures involving limited cell and target gene copy numbers. Purified leukocytes and myeloid colonies derived from patients with chronic myelogenous leukemia (CML) in chronic phase were used for direct RT-PCR. Purified cells and colonies were lysed using a small quantity of DEPC-treated water containing RNasin as an RNA inhibitor. The untreated lysate was either used immediately for RT-PCR or frozen at -70 degrees C for later use. By this method we were able to consistently amplify bcr-abl transcripts from as few as 10 cells. No noticeable difference was observed between products amplified from fresh and frozen samples.